DEVELOPMENT OF THE CITRA NURSING MODULE (COMMUNICATION THROUGH INTERACTIVE THERAPEUTIC AND REFLECTIVE STORYTELLING APPROACH) TO REDUCE ANXIETY IN HOSPITALIZED PRESCHOOL CHILDREN - Citra Suraya; Aris Citra Wisuda; Tukimin bin Sansuwito; Regidor III Dioso (Journal Of Nursing Science Research, 2025)
Background: Hospitalization often triggers significant anxiety in preschool children due to unfamiliar environments, separation from parents, and invasive procedures. Interactive and therapeutic communication approaches are essential to support children’s emotional stability during care. Objective: This study aimed to develop and evaluate the CITRA Nursing Module (Communication through Interactive Therapeutic and Reflective Storytelling Approach) as an intervention to reduce hospitalization anxiety in preschool children. Methods: This research employed a Research and Development design using the ADDIE model. The module was developed through literature review, expert validation, and preliminary observations, then tested on 46 hospitalized preschool children at Siti Khadijah Islamic Hospital Palembang between February and July 2025. Anxiety levels were measured before and after the intervention using a validated anxiety instrument for preschoolers. Paired statistical tests were used to determine intervention effectiveness. Results: The CITRA module was effective in reducing hospitalization anxiety. Post-intervention scores showed a significant decrease, indicating improved emotional comfort and coping abilities. Feedback from nurses and parents confirmed the module’s feasibility, practicality, and acceptability in clinical practice. Conclusion: The CITRA Nursing Module is an effective intervention for reducing hospitalization anxiety in preschool children. Its implementation has the potential to strengthen therapeutic communication and support child-centered hospitalization practices. Further research with a larger and more diverse population is recommended to enhance the generalizability of the findings.